Penerapan Projek Penguatan Profil Pelajar Pancasila Tema Kearifan Lokal (P5) Di Kelas IV SD Negeri 5 Sindue - Risnawati 2502; Andi Imrah Dewi (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
The main aim of this research is to find out how the project to strengthen the profile of Pancasila students with the theme of local wisdom is implemented at SD Negeri 5 Sindue. This research uses qualitative research with a descriptive approach. The subjects of this research were class IV homeroom teachers and class IV students at SD Negeri 5 Sindue. The data collection techniques used in this research are questionnaires, interviews, observation and documentation. The data analysis used in this research is data reduction, data presentation, drawing conclusions, and descriptive analysis. The results of research and analysis of research data show that students can appreciate and love local wisdom in their area through implementing a project to strengthen the profile of Pancasila students in class IV of SD Negeri 5 Sindue. This is confirmed by the average questionnaire score which is at 80.76% or the high category, then reinforced by interview data which shows that there has been a change in students' attitudes through the implementation of the project to strengthen the profile of Pancasila students with the theme of local wisdom. Apart from that, student observation data also shows the same results, where all 4 sub-indicators show that students appreciate and love local wisdom more in their area through implementing a project to strengthen the profile of Pancasila students with the theme of local wisdom in class IV of SD Negeri 5 Sindue.